1988
DOI: 10.1152/jappl.1988.64.4.1333
|View full text |Cite
|
Sign up to set email alerts
|

Lipid peroxidation and scavenger enzymes during exercise: adaptive response to training

Abstract: This study was designed to determine whether endurance training would influence the production of lipid peroxidation (LI-POX) by-products as indicated by malondialdehyde (MDA) at rest and after an acute exercise run. Additionally, the scavenger enzymes catalase (CAT) and superoxide dismutase (SOD) were examined to determine whether changes in LIPOX are associated with alterations in enzyme activity both at rest and after exercise. Male Sprague-Dawley rats (n = 32) were randomly assigned to either trained or se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
160
1
14

Year Published

1996
1996
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 317 publications
(189 citation statements)
references
References 0 publications
14
160
1
14
Order By: Relevance
“…Catalase With only a few exceptions (29,74,119,120), most studies report no significant alteration in CAT activity with acute exercise or chronic training (8,13). With a catalytic mechanism similar to SOD, CAT activity might be expected to increase during exercise due to increased H202 production.…”
Section: Antioxidant Enzymesmentioning
confidence: 99%
“…Catalase With only a few exceptions (29,74,119,120), most studies report no significant alteration in CAT activity with acute exercise or chronic training (8,13). With a catalytic mechanism similar to SOD, CAT activity might be expected to increase during exercise due to increased H202 production.…”
Section: Antioxidant Enzymesmentioning
confidence: 99%
“…Other studies report adaptations induced by endurance training in variables responsible for the improvement of oxidative metabolism such as a coordinated increase in the capacity for fatty acid, carbohydrate, ketone and amino acid oxidation and in the enzymatic pathways required for handling the reducing equivalents (9)(10)(11). Despite the beneficial adaptations induced by physical exercise, which leads to qualitative changes in muscle metabolism, an important side effect should be noted, such as the increased generation of reactive oxygen species (ROS), especially during exhaustive and unaccustomed exercise (12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, Alessio and Goldfarb (20) have shown that the training on treadmill in young rats increases the CS activity in the gastrocnemius twice more than in the control group.…”
Section: Discussionmentioning
confidence: 88%